Prática em extinção ou em processo de renovação?: um estudo sobre a supervisão educacional - Karla Vignoli Viegas Barreira (2006)
This research intends to investigate the process of transformation of the Educator-Supervisor function in the last years, in the public and private schools, analyzing and comparing their performance with the one of the Pedagogic Coordinator, their presumed successor in the municipal schools of Belo Horizonte. In Belo Horizonte, the implantation of the project Escola Plural in 1995 in the municipal schools, suppressed the School Supervisor's function and transferred their tasks to Teacher-Coordinators, in a process that aimed to give the teacher a superior autonomy and to enlarge their performance in the school. In this new proposal, the process of power decentralization was implemented inside the school, starting to elect the Coordinator with wider functions than those of the Educational Supervisor. Such event has been provoking serious questioning concerning the directions that will be taken by the profession. The pertinence of the discussion, that is not new at this time, stands in the survival of the profession, what sets this subject in a privileged degree of analysis. Through some studies of cases performed with an Educational Supervisor and two Pedagogic Coordinators of the private and public municipal schools of Belo Horizonte, respectively, we tried to elucidate how the practices of these professional occur at the present time. The data come from the observations of the three researched professionals performance, from the answers given by them and by other educators, during interviews and through consultation of documents. The analysis is based in the literature of the Educational Supervision (Celestino Silva Jr., Naura Ferreira, Nilda Alves, Regina Garcia, Myrtes Alonso, Antônia Medina, Demerval Saviani, José Carlos Libâneo, Mary Rangel, Mirian Grinspun, Marileusa Fernandes, Vera Placco, Ana Maria Franz, and others). The conclusion is elected that the Pedagogic Coordinators at the municipal schools of Belo Horizonte, to substitute the Educational Supervisors, still didnt build a new proposal of performance that differentiates them substantially of the old supervision. Both supervisors, in the public and in the private school still now were not able to shape a new model of supervision which give them a new identity.